Point mutations 5' to the tRNA selenocysteine TATA box alter RNA polymerase III transcription by affecting the binding of TBP. - Myslinski, E (1993)
The selenocysteine tRNA(Sec) gene possesses two external promoter elements, one of which is constituted by a strong TATA box. Point mutant analysis performed in this study led to the conclusion that the functional TATA promoter actually encompasses the sequence -34 GGGTATAAAAGG-23. Individual changes at T-31 do not affect transcription much. Position T-29 is less permissive to mutation since transversion to a G, for example, is less well tolerated than at T-31. Interestingly, a double point mutation, converting GG(-33/-32) to TT, causes abrogation of transcription in vivo and severe reduction of transcription in vitro with human TBP. Therefore, data obtained underscore the fact that, in the Xenopus tRNA(Sec), these two Gs are an integral part of the TATA promoter. Gel retardation experiments indicate that the GG to TT substitution, which led human TBP to lose its ability to support efficient transcription in vitro, correlates with the appearance of an altered pattern of retarded complexes. Altogether, the data presented in this report support a model in which TBP interacts directly with the TATA element of the tRNA(Sec) gene, in contrast to the type of interaction proposed for classical TATA-less tRNA genes.